2014
DOI: 10.1039/c4ra00213j
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane microcapsules for self-healing paint coatings

Abstract: Polyurethane microcapsules containing water-borne polyurethane (PU) paint as a core material for self-repairing protection coatings were successfully manufactured via interfacial polymerization of diol–diisocyanate prepolymer and 1,4-butanediol as a chain extender in an emulsion solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 33 publications
(34 reference statements)
2
67
1
Order By: Relevance
“…Microcapsules, one of the controlled release techniques, have been used in many fields, such as food, medicine, pesticides, environmental engineering, biological Engineering, cosmetics, and coatings, among others. A controlled release formulation, microcapsules are small particles with sizes between 1 and 100 μm that contain an active agent encapsulated by a natural membrane or a polymeric membrane synthesized by physical methods, chemical methods, or a combination of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Microcapsules, one of the controlled release techniques, have been used in many fields, such as food, medicine, pesticides, environmental engineering, biological Engineering, cosmetics, and coatings, among others. A controlled release formulation, microcapsules are small particles with sizes between 1 and 100 μm that contain an active agent encapsulated by a natural membrane or a polymeric membrane synthesized by physical methods, chemical methods, or a combination of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…This powder‐coating method has advantages in terms of environmental pollution because it can cure a polymer at a low temperature (below 150°C) without a volatile solvent. C 12 diacid has traditionally been used as a curing agent for glycidyl methacrylate acrylic (GMA) used in automotive body coatings; however, recent tests have shown that GMA cured with C 18 long chain diacid has a better impact resistance . The longer and more flexible C 18 methylene chain increases the flexibility and impact resistance of the cured GMA.…”
Section: C3–c30 Oil Derivativesmentioning
confidence: 99%
“…In the watery environment chromium can exist in either as Cr(VI) or Cr(III) of which, the 8 Cr(VI) is known to be profoundly lethal, mutagenic and cancer-causing [4][5][6]. Its vicinity in 9 nature also poses huge risk to oceanic life and also to open wellbeing [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the watery environment chromium can exist in either as Cr(VI) or Cr(III) of which, the 8 Cr(VI) is known to be profoundly lethal, mutagenic and cancer-causing [4][5][6]. Its vicinity in 9 nature also poses huge risk to oceanic life and also to open wellbeing [5,7]. As per the standards, 10 the maximum permissible limit of Cr(VI) for discharge to inland surface water and portable 11 water is 0.1 mg L -1 and 0.05 mg L -1 respectively [7][8].…”
Section: Introductionmentioning
confidence: 99%